Mempelajari Konsep Moral Dewasa Muda Jakarta dengan Pilihan Tidak Beragama - Raymond Godwin (Bina Nusantara University, 2013)
This article aims to determine the unreligious people's thought relating to moral and other things that affect their thought. The research method used was qualitative method. The research was conducted by interviewing three participants, one woman and two men. All three participants were in the age range 22 to 23 years old. The results showed that unreligious people see moral as an important thing in human relations. For them, moral is a form of quality values owned by a person, which is reflected in the behavior, the treatment of other people, and her/himself. Their moral concepts are influenced by each person's cognitive factors and social experiences.